Molecular detection of Lotmaria passim in intestine of Japanese honeybees (Apis cerana japonica) - Suzuki, Akihiko; Sakamoto, Yoshiko (Entomological science, 2024)
ABSTRACT Crithidia mellificae and Lotmaria passim are trypanosomatids that infect honeybees, and many studies suggest that both parasites contribute to the decline in the honeybee population. The Japanese honeybee (Apis cerana japonica) is a native honeybee that inhabits various areas of Japan and is one of the most important pollinators. Both parasites have been well studied in the western honeybee (Apis mellifera) but have been poorly investigated in A. c. japonica. The present study investigated the presence of C. mellificae and L. passim in one feral and six managed A. c. japonica colonies at three different institutes. Five out of seven colonies were polymerase chain reaction‐positive for L. passim (71.4%); however, C. mellificae was not detected. Four of the five colonies were positive in both the midgut and hindgut, but one was positive only in the hindgut. A homology search and phylogenetic tree of the glycosomal glyceraldehyde‐3‐phosphate dehydrogenase (gGAPDH) and cytochrome b (Cytb) genes obtained in this study indicated that the sequences belonged to L. passim. The results of this study emphasize concerns regarding the health of this ecologically important pollinator and the importance of further investigation of the prevalence of L. passim in A. c. japonica in a wider area of Japan. We investigated the presence of two trypanosomatids, Crithidia mellificae and Lotmaria passim, in feral and managed Apis cerana japonica colonies. This is the first study to molecularly detect L. passim from A. c. japonica.